RETHINKING THE DEVELOPMENT OF GHANA: THE ANSWER IS HERE - John, TUMAKU (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 20 (2018): Annales Universitatis Apulensis Series Oeconomica, 2018)
Ghana is struggling to become a middle income economy even with discovery of oil and gas in commercial quantity. The paper presented an alternative approach on how to rethink and develop Ghana using mix approach. In this paper, the researcher attempt to compare Ghana’s GNI to her cohort especially China in 1963 and 2016 and how China developed with greater GNI than Ghana. We also examine the relationship between GDP growth and other factors such as Inflation, Foreign Direct Investment (FDI), Import and Export in Ghana. The researcher found FDI and Inflation to have negative relationship on GDP but Import and export have positive impact on GDP. We concluded that, Ghana must learn from developed world and tap from the experience of Chinese, should desist from exporting raw product and move from import economy to an export one like China in other to improve our balance of trade.